Suppression of the formation of furan by antioxidants during UV-C light treatment of sugar solutions and apple cider. (15th December 2018) - Hu, Gaofei; Liu, Huaizhi; Zhu, Yan; Hernandez, Marta; Koutchma, Tatiana; Shao, Suqin
Highlights: Furan could be formed in sugar solutions and apple cider during UV-C treatment. Fructose was the predominant precursor of furan during UV-C treatment. Antioxidants could suppress the formation of furan during UV-C treatment. Abstract: Furan, which has been identified as a carcinogenic risk for humans, can be induced in different foods by UV-C light. In this study, we hypothesized that furan was produced by a UV light-induced free radical mechanism and antioxidants could suppress its formation. Our results demonstrated that, by adding antioxidants, such as butylated hydroxyl toluene, ascorbic acid or gallic acid, to simulated juice or apple cider during UV-C treatment, amounts of furan were significantly reduced. For example, the concentration of furan produced in apple cider by UV-C at 9.0 J/cm 2 was 636 ppb but was less than 20 ppb with 0.25 ppm butylated hydroxyl toluene present, less than 3 ppb with 0.5% (w/v) ascorbic acid, and less than 1.0 ppb with 0.5% (w/v) gallic acid. These findings confirmed that antioxidants can be used as a safe and simple mitigation measure to control furan production in fruit drinks exposed to UV-light.